THE ORIGIN OF OLDHAMITE IN UNEQUILIBRATED ENSTATITE CHONDRITES - Crozaz G.; Lundberg L.L. (My University, 1995)
We report the results of an ion probe study of rare earth elements (REEs) in six unequilibrated enstatite chondrites. Oldhamite is confirmed as the major but not the only REE carrier in these meteorites. Data are also provided for other minerals (enstatite, niningerite, and alabandite) that carry detectable amounts of REEs. Although the variety of REE patterns in oldhamite is not as extreme as in hibonite, there are seven distinct REE patterns (four of which form a continuum) that characterize most oldhamite grains from E chondrites. Two of these patterns (F and G) were each found in only one weathered grain. There is no correlation between REE pattern and oldhamite petrologic setting. Our trace element data are used to evaluate earlier work and a number of elements (Zr, Y, Sc, REEs, Sr, Se, and probably Sb and Cs), including both refractory and volatile species under oxidizing conditions, are found enriched in oldhamite. A comparison of REE patterns with the results of equilibrium condensation calculations indicates that nebular processes were important in determining the composition of the oldhamite precursors, whereas metamorphic processes also affected oldhamite compositions. Enrichments of chalcophiles are not necessarily due to interaction of oldhamite with nebular gas at low temperatures, as previously suggested. Oldhamite, like hibonite, was formed from melts whose trace element compositions were determined by high temperature transient events in the solar nebula.